2016
DOI: 10.1039/c6sm02171a
|View full text |Cite
|
Sign up to set email alerts
|

Lipid membrane-assisted condensation and assembly of amphiphilic Janus particles

Abstract: Amphiphilic Janus particles self-assemble into complex metastructures, but little is known about how their assembly might be modified by weak interactions with a nearby biological membrane surface. Here, we report an integrated experimental and molecular dynamics simulation study to investigate the self-assembly of amphiphilic Janus particles on a lipid membrane. We created an experimental system in which Janus particles are allowed to self-assemble in the same medium where zwitterionic lipids form giant unila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In this regard, it is very important to understand the biological interaction of Janus nanoparticles to ensure their successful clinical trial. Several simulation and experimental studies reported in the literature exhibit that Janus particles show different biological interactions as compared to homogeneous particles owing to their surface anisotropy. , These studies help us to rationally design Janus particles, with the desired biological properties and use them to understand and manipulate different cellular functions as required.…”
Section: Janus Nanoparticles For Biomedical Applicationsmentioning
confidence: 99%
“…In this regard, it is very important to understand the biological interaction of Janus nanoparticles to ensure their successful clinical trial. Several simulation and experimental studies reported in the literature exhibit that Janus particles show different biological interactions as compared to homogeneous particles owing to their surface anisotropy. , These studies help us to rationally design Janus particles, with the desired biological properties and use them to understand and manipulate different cellular functions as required.…”
Section: Janus Nanoparticles For Biomedical Applicationsmentioning
confidence: 99%
“…21,22 Current synthesis methods of Janus particles allow to adjust surface properties such as hydrophobicity, hydrophilicity, and charge 23,24 that affect the adhesiveness to vesicle membranes. 25 The simulation data of Figure 1 show repulsive curvature-mediated interactions of two Janus particles that are adsorbed at the inside of a vesicle. In our simulated annealing Monte Carlo (MC) simulations, the bending energy of the vesicle is minimized at different, fixed distances of the two particles (see Supporting Information for further information).…”
Section: Max Planck Institute Of Colloids and Interfaces • Authormentioning
confidence: 99%
“…The strongly adhesive cap of adsorbed Janus particles is fully covered by the vesicle membrane. In experiments, Janus particles with strongly adhesive and nonadhesive surface areas have been realized by partial coating with ligands that bind to receptors anchored in cell membranes. , Current synthesis methods of Janus particles allow to adjust surface properties such as hydrophobicity, hydrophilicity, and charge , that affect the adhesiveness to vesicle membranes …”
mentioning
confidence: 99%
“…Yet we currently have little knowledge about how the surface or structural anisotropy of Janus particles might affect their interaction with biological systems. Simulation studies have predicted that when Janus particles interact with biological systems, their behavior deviates from that of uniform particles due to their surface anisotropy. We and other groups have also demonstrated this experimentally in a few recent studies. ,, However, more studies from both theoretical and experimental perspectives are necessary to fully elucidate the role the anisotropy of Janus particles plays in their biological behavior. With such fundamental knowledge, we may then be able to rationally design Janus particle-based materials with desirable biological properties.…”
Section: Introductionmentioning
confidence: 98%